Estrogen Signaling and Portopulmonary Hypertension: The Pulmonary Vascular Complications of Liver Disease Study (PVCLD2). Issue 2 (29th September 2020) - Al‐Naamani, Nadine; Krowka, Michael J.; Forde, Kimberly A.; Krok, Karen L.; Feng, Rui; Heresi, Gustavo A.; Dweik, Raed A.; Bartolome, Sonja; Bull, Todd M.; Roberts, Kari E.; Austin, Eric D.; Hemnes, Anna R.; et al.
Abstract : Background and Aims: Portopulmonary hypertension (POPH) was previously associated with a single‐nucleotide polymorphism (SNP) rs7175922 in aromatase (cytochrome P450 family 19 subfamily A member 1 [ CYP19A1 ]). We sought to determine whether genetic variants and metabolites in the estrogen signaling pathway are associated with POPH. Approach and Results: We performed a multicenter case‐control study. POPH patients had mean pulmonary artery pressure >25 mm Hg, pulmonary vascular resistance >240 dyn‐sec/cm −5, and pulmonary artery wedge pressure ≤15 mm Hg without another cause of pulmonary hypertension. Controls had advanced liver disease, right ventricular (RV) systolic pressure <40 mm Hg, and normal RV function by echocardiography. We genotyped three SNPs in CYP19A1 and CYP1B1 using TaqMan and imputed SNPs in estrogen receptor 1 using genome‐wide markers. Estrogen metabolites were measured in blood and urine samples. There were 37 patients with POPH and 290 controls. Mean age was 57 years, and 36% were female. The risk allele A in rs7175922 ( CYP19A1 ) was significantly associated with higher levels of estradiol ( P  = 0.02) and an increased risk of POPH (odds ratio [OR], 2.36; 95% confidence interval [CI], 1.12‐4.91; P  = 0.02) whereas other SNPs were not. Lower urinary 2‐hydroxyestrogen/16‐α‐hydroxyestrone (OR per 1‐ln decrease = 2.04; 95% CI, 1.16‐3.57; P  = 0.01), lower plasma levels of dehydroepiandrosterone‐sulfate (OR per 1‐ln decrease = 2.38; 95% CI, 1.56‐3.85; P  < 0.001), and higher plasma levels of 16‐α‐hydroxyestradiol (OR per 1‐ln increase = 2.16; 95% CI, 1.61‐2.98; P  < 0.001) were associated with POPH. Conclusions: Genetic variation in aromatase and changes in estrogen metabolites were associated with POPH.